Effect of a probiotic bacterium supplemented feed on survival and growth of fry of two ornamental fishes, Pterophyllum scalare and Metynnis schreitmuelleri - Singh, R K; Chawan, J B; Vartak, V R; Belsare, S G (Indian Journal of Fisheries, 2011)
A 30 day experiment conducted in the laboratory to evaluate the effects of aprobiotic, Lactobacillus incorporated diet on the fry of angel fish (Pterophyllum scalare) and silver dollar (Metynnis schreitmuelleri) indicated improvement both in the growth rate and survival of the two species. The feed comprising 0.1, 0.2 and 0.3% probiotic in diets A, B, and C was fed to the fish while, the diet D served as control. The diet containing 0.2% probiotic (B) was observed to be best with regard to weight gain, length increase and survival